Effectiveness of dimple microtextured copper substrate on performance of Sn-0.7Cu solder alloy - Siti Faqihah, Roduan; Juyana, A. Wahab; Mohd Arif Anuar, Mohd Salleh; Nurul Aida Husna, Mohd Mahayuddin; Mohd Mustafa, Al Bakri Abdullah; Aiman, Mohd Halil; Amira Qistina Syamimi, Zaifuddin; Mahadzir, Ishak; Sandu, Andrei Victor; Baltatu, Mădălina Simona; Vizureanu, Petrica (MDPI, 2023)
This paper elucidates the influence of dimple-microtextured copper substrate on the performance of Sn-0.7Cu solder alloy. A dimple with a diameter of 50 µm was produced by varying the dimple depth using different laser scanning repetitions, while the dimple spacing was fixed for each sample at 100 µm. The dimple-microtextured copper substrate was joined with Sn-0.7Cu solder alloy using the reflow soldering process. The solder joints’ wettability, microstructure, and growth of its intermetallic compound (IMC) layer were analysed to determine the influence of the dimple-microtextured copper substrate on the performance of the Sn-0.7Cu solder alloy. It was observed that increasing laser scan repetitions increased the dimples’ depth, resulting in higher surface roughness. In terms of soldering performance, it was seen that the solder joints’ average contact angle decreased with increasing dimple depth, while the average IMC thickness increased as the dimple depth increased. The copper element was more evenly distributed for the dimple-micro-textured copper substrate than its non-textured counterpart.